Increased spontaneous recombination in RNase H2-deficient cells arises from multiple contiguous rNMPs and not from single rNMP residues incorporated by DNA polymerase epsilon - Anastasiya Epshtein; Catherine J. Potenski; Hannah L. Klein (Microbial Cell)
Ribonucleotides can become embedded in DNA from insertion by DNA polymerases, failure to remove Okazaki fragment primers, R-loops that can prime replication, and RNA/cDNA-mediated recombination. RNA:DNA hybrids are removed by RNase H enzymes. Single rNMPs in DNA are removed by RNase H2 and if they remain on the leading strand, can lead to mutagenesis in a Top1-dependent pathway. rNMPs in DNA can also stimulate genome instability, among which are homologous recombination gene conversion events. We previously found that, similar to the rNMP-stimulated mutagenesis, rNMP-stimulated recombination was also Top1-dependent. However, in contrast to mutagenesis, we report here that recombination is not stimulated by rNMPs incorporated by the replicative polymerase epsilon. Instead, recombination seems to be stimulated by multiple contiguous rNMPs, which may arise from R-loops or replication priming events.